Continous Rituximab treatment for recurrent diffuse alveolar hemorrhage in a patient with systemic lupus erythematosus and antiphosholipid syndrome. (2017) - Aakjær, Signe; Bendstrup, Elisabeth; Ivarsen, Per; Madsen, Line Bille
Abstract: Diffuse alveolar hemorrhage (DAH) is a rare but potentially fatal complication in systemic lupus erythematosus (SLE). DAH is typically characterized by hemoptysis, dyspnea, new infiltrates on chest x-rays or CT-scans and a drop in hemoglobin. DAH is seen in less than 2% of patients with SLE and carries a high acute mortality risk of up to 70–90%. The current treatment of DAH is high-dose intravenous corticosteroids, cyclophosphamide and extensive supportive care. Plasmapheresis is also often considered in the treatment. A few case reports have described patients with SLE and DAH in whom a single series of Rituximab (RTX), a specific anti-CD20-antigen B-cell antibody, successfully has been used to treat DAH. We here present the first case of a patient with combined SLE, antiphospholipid syndrome (APS) and recurrent DAH who was successfully controlled by continued treatment with RTX.